2022
DOI: 10.1111/iju.14776
|View full text |Cite
|
Sign up to set email alerts
|

Clean intermittent catheterization in long‐term management of neurogenic bladder in spinal cord injury: Patient perspective and experiences

Abstract: Bladder dysfunction due to spinal cord injury has a significant impact on the overall health and quality of life of an individual. Clean intermittent catheterization is the gold standard for bladder management and is recommended due to having the lowest complication rate. Transitions from intermittent catheterization to other less optimal strategies, such as indwelling catheter, are quite common. However, the research documenting patient perspectives, and epidemiological and demographic factors related to such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Especially, optimizing ISC away from home is a major challenge. Joshi et al 17 reported that 63.41% of patients with SCI had difficulty in carrying out CIC away from home, and the reason for difficulty of the majority of the patients was toilet facilities, followed by time regulation and dependence. If ISC is difficult to perform when away from home, the use of i‐IDC may be considered in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, optimizing ISC away from home is a major challenge. Joshi et al 17 reported that 63.41% of patients with SCI had difficulty in carrying out CIC away from home, and the reason for difficulty of the majority of the patients was toilet facilities, followed by time regulation and dependence. If ISC is difficult to perform when away from home, the use of i‐IDC may be considered in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Although seems simple and straightforward, assisted bladder emptying, including Credé or Valsalva maneuver, is not suggested due to the considerations of safety and effectiveness. Nowadays, CIC is considered as the “gold standard for bladder emptying.” 26 …”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, CIC is considered as the "gold standard for bladder emptying." 26 Maintaining low pressure during bladder retention is important. Antimuscarinic drugs, botulinum toxin injection, electrical stimulation, and bladder augmentation are all effective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The acute stage of spinal cord injury patients is the stage of spinal cord shock[ 16 ]. The bladder loses spinal cord innervation, resulting in complete paralysis of the detrusor muscle of the bladder, loss of contraction and relaxation functions, and reduced tension of the urethral sphincter.…”
Section: Rehabilitation Nursing Measuresmentioning
confidence: 99%